Ecology Needs Theology - Siegenthaler, David (Dialog, 2003)
A primary purpose of theology is the explication of the relationship of Creation to the transcendent for the sake of responsible action in the world. Environmental policy arenas need a perspective that can take them beyond a more limited utilitarianism. Ecology needs theology. We can appreciate to a much greater extent today than we could a generation ago that all theologies are products of particular people within particular social, cultural, historical, geographical situations. To do theology adequately, it is clearer now that many perspectives must be considered—both within and outside one's own tradition. Theology must be conversational. One's assertions of values and proposed actions must be weighed against the assertions of others. Only through such engagement will theology be meaningful to lives that must be lived with integrity in a world of manifold ambiguities. That world is the whole world in which human community is sustained and to which human beings are responsible. The practical effects of theological engagement will be to help us all find a better “common good” than may be obtained otherwise.